1987
DOI: 10.3758/bf03208230
|View full text |Cite
|
Sign up to set email alerts
|

Orientation discrimination as a function of orientation and spatial frequency

Abstract: Orien~tion discrimination was measured with a yes-no signal detection procedure at two reference orientations, 90° and 45°. For the first of two experiments, the stimuli were disk-shaped gratings, 2.5 ° in diameter. Their spatial frequencies ranged from 1.8 cpd to 17.6 cpd. For the second experiment, the stimuli were either gratings or bars consisting of the center cycle of the corresponding grating. As expected, the results showed a highly significant reference orientation factor, with smaller just noticeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…We observed that performance in identification of the oblique orientation could be improved dramatically with practice. Initial thresholds were similar to those reported by others, and higher than reported for vertical or horizontal references (Vogels & Orban, 1985;Matin, Rubsamen & Vannata, 1987), in line with the 'oblique effect' reported for line orientation discrimination and grating contrast sensitivity (Andrews, 1967;Appelle, 1972;Orban et al 1984). Our finding of a dramatic decrease in threshold for the oblique orientation with practice may not apply to the vertical and horizontal orientation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that performance in identification of the oblique orientation could be improved dramatically with practice. Initial thresholds were similar to those reported by others, and higher than reported for vertical or horizontal references (Vogels & Orban, 1985;Matin, Rubsamen & Vannata, 1987), in line with the 'oblique effect' reported for line orientation discrimination and grating contrast sensitivity (Andrews, 1967;Appelle, 1972;Orban et al 1984). Our finding of a dramatic decrease in threshold for the oblique orientation with practice may not apply to the vertical and horizontal orientation.…”
Section: Discussionsupporting
confidence: 91%
“…Initial thresholds were similar to those reported by others, and higher than reported for vertical or horizontal references (Vogels & Orban, 1985;Matin, Rubsamen & Vannata, 1987), in line with the 'oblique effect' reported for line orientation discrimination and grating contrast sensitivity (Andrews, 1967;Appelle, 1972;Orban et al 1984 Orban (1985) that the effects of practice upon orientation discrimination originate at the sensory level and not in the decision process, and cannot be attributed to a change in memory noise, attention or accommodation. Our study elaborated upon these findings to investigate the localization of this form of human perceptual learning in the visual pathway.…”
Section: Discussionsupporting
confidence: 73%